Brassinosteroid phytochormones as regulators of plant growth and modulators of pesticide and fertilizer activity - Nikolić, Bogdan; Waisi, Hadi; Jovanović, Vladan; Dragičević, Vesna; Djurović, Sanja (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
The mode of action of agrochemicals on plants implies the totality of their effect on plant metabolism, growth and development. The effects of different doses of 24-epibrassinolide (24-EBL) as a class of brassinosteroid phytohormones on growth and other physiological processes inmaize plants during different development stages are reviewed in order to assess the influence ofthese agrochemicals on various factors determining the yield of maize as an important agriculturalcrop. In addition, several examples are given of the effects of these phytohormones on other crops, fruits and vegetables, in terms of their effect on yield, yield quality, and increase in crop resistance to some types of stress. Own results are discussed in the context of other literature data.
Keywords: Phytohormones; Brassinosteroids; Plant growth; Plant nutrition; Plant protection